Sistem Pendeteksi Kebocoran LPG Untuk Smarthome Berbasis IoT dengan Metode Fuzzy - Ciksadan Ciksadan; Suroso Suroso; Yuris Ramadhona (STMIK Budi Darma, 2020)
Common problems that often occur in users of LPG gas, especially LPG gas with a size of 3kg are the wrong way of installation and the leakage of gases that are not detected by the sense of human smell that often causes fires. Fires were triggered due to sparks or even by an electronic device that is still on due to manual operation of electronic devices so that users forget to shut down the device when not in use. Therefore, an integrated technology of a system that can control electronic devices automatically and monitor LPG gas leakage thereby reducing the risk of gas leaks that are not detected by the sense of smell of humans and the risk of fire due to electronic devices that continue to ignite when not in use. The sensors used in this system are PIR sensors to detect human presence and MQ6 sensors to detect the presence of leaky gas and Raspberry pi as processors based on Internet Of Things using the fuzzy logic method as the MQ6 sensor input receiver. This system will automatically turn on the lights when a human being is detected and turn off the lights when there are no humans, besides this system will also automatically turn on the buzzer as a warning when a gas leak is detected. Data received by raspberry pi will be stored on the web server and sent to the user's e-mail in the form of gas leak status and electronic device status